Monitoring Authenticity and Quality of Concentrated Grape Must - Nonna V. Gnilomedova; Antonina V. Vesyutova; Nadezhda S. Anikina; Marianna V. Ermikhina; Veronica A. Oleinikova (Техника и технология пищевых производств, 2024)
The Russian wine industry permits the use of concentrated grape must. Due to its shortage on the market, it often becomes subject to adulteration. The article introduces a comprehensive system for assessing the quality of concentrated grape must that prevents adulteration of semi-dry and semi-sweet wines. The research featured 446 samples of fresh and concentrated grape must, commercial preparations of concentrated white grape must, and sugar or glucose-fructose syrups. The method of high-performance liquid chromatography made it possible to identify the profile of organic acids and sugars. After introducing authentic concentrated grape must, the samples were tested for colloidal turbidity and crystalline destabilization. The authentic samples retained the chemical composition of the original grape variety, as evidenced by such authenticity markers as pH, disaccharide content, tartaric and malic acids, and glucose-fructose index. In the adulterate samples, these values did not fit the standard limits. The experiment involved 179 samples of commercial preparations: 21% proved to be mixes of authentic must with other products; 9% proved to be syrup substitutes, and 1% was concentrated apple juice. Authentic concentrated must aggravated the trend to colloidal opacity (17%) and crystalline destabilization (13%); a combination of both trends occurred in 13%. Low-quality preparation of fresh grape must before vacuuming increased the content of high- molecular components, tartrate anions, and potassium cations in the concentrated product. The following two-step assessment of concentrated grape must quality made it possible to adopt a rational technological solution: I – confirming the grape origin; II – assessing the effect of the authentic product on the colloidal and crystalline stability of wine. This protocol demonstrated a good potential for ensuring the authenticity and bottling stability of semi-dry and semi-sweet wines.